Leaning against the wind and crisis risk - Moritz Schularick; Lucas ter Steege; Felix Ward (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
Can central banks defuse rising stability risks in financial booms by leaning against the wind with higher interest rates? This paper studies the state-dependent effects of monetary policy on financial crisis risk. Based on the near-universe of advanced economy gonancial cycles since the 19th century, we show that discretionary leaning against the wind policies during credit and asset price booms are more likely to trigger crises than prevent them.
Keywords: E44; E50; G01; G15; N10; 330; financial stability; monetary policy; local projections